2015
DOI: 10.1097/ede.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian Hormone and Lifestyle, Reproductive, and Environmental Factors Among Women in Rural South Africa

Abstract: Background Few data exist regarding antiMüllerian hormone, a marker of ovarian reserve, in relation to environmental factors with potential ovarian toxicity. Methods This analysis included 420 women from Limpopo, South Africa studied in 2010–2011. Women were administered comprehensive questionnaires, and plasma concentrations of antiMüllerian hormone and DDT were determined. We used separate multivariable models to examine the associations between natural log-transformed antiMüllerian hormone concentration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 38 publications
6
47
0
Order By: Relevance
“…Few studies have considered the impact of household air pollution on reproductive outcomes. One previous study of South African women found no association between AMH levels and self-reported indoor cooking over wood fires (15). However, this study did not consider artificial firelogs, which are manufactured logs composed of pressed sawdust and wax.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Few studies have considered the impact of household air pollution on reproductive outcomes. One previous study of South African women found no association between AMH levels and self-reported indoor cooking over wood fires (15). However, this study did not consider artificial firelogs, which are manufactured logs composed of pressed sawdust and wax.…”
Section: Discussionmentioning
confidence: 90%
“…Few previous studies have considered adult ETS exposure with respect to AMH levels and the two that did found no association with AMH (15, 19). Though active smoking is usually considered a greater health risk than ETS, there are different levels of the various compounds in sidestream compared to mainstream smoke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For each gene (BRCA1 and BRCA2), a difference in mean AMH concentration between mutation carriers and non-carriers was tested by linear regression, modelling the natural logarithm of AMH as the outcome variable and carrier status as the explanatory variable. This log transformation was applied to correct for the asymmetry in the distribution of AMH values, as consistently reported in other studies (Su et al, 2013;Whitworth et al, 2015). The exponential of the regression coefficient for carrier status (and its 95% confidence interval (CI) limits) was taken as an estimate of mean AMH concentration on the natural scale for carriers relative to non-carriers.…”
Section: Methodsmentioning
confidence: 99%